Experiências neoliberais: Brasil, Argentina, Chile e México - Ditticio, Claudio (2007)
In this study, are discussed the experiences of Brasil, Argentina, Chile and México, mainly after their implementation of Neoliberalism, starting from the analyses of alternative economic thoughts related to liberalism and state intervention on economy. To do so, the histories of that countries from the beginning of last century, are revisited in order to identify the reasons behind the implementation of those system, as well as to verify the results hitherto. Every nation has a different history of accomplishments and sufferings. The main macroeconomic goals are related to monetary stabilization, sustained growth and employment, with fair distribution of the resources and economic and social benefits to the population. Trying to achieve those results, several alternative economic schools and related practices have been implemented in several regions. Many analysts and critics pointed that the end of the communist experience in Soviet Union was a confirmation of the best approach brought by the capitalist system of production and distribution of goods and services. All the countries had to do was open their economies for the free transactions between the nations, in every aspect of their economic activities. The results have been, in the beginning of a new century, of both successes and defeats. The data show that even for the countries with better economic performance, several problems are observed concerning social aspects related to low salaries and bad income distribution. With the beginning of a new century, the interest lies in knowing what to expect in terms of benefits for the present and the coming generations to Brazil concerning the adoption of the procedures recommended under the Neoliberals approach here and in other main Latin American countries. We also look for information to confirm the future of Neoliberalism or eventually its substitution by other kind of theories and practices to assure sustained growth and stability to the global economy. Finally, it is discussed the impossibility to implement a pure and closed model of economic thought, without considering the subjects related to the history and specificities of a particular society